Pendampingan Mahasantri dalam Meningkatkan Pemahaman Nahwu melalui Program Musyawarah - Rohman, M. Fathor; Nashihin, Nashihin; Ulfa, Maria; Shomad, H. Abdus (Universitas Sunan Drajat Lamongan, Indonesia, 2025)
This community engagement program aimed to enhance the understanding of Arabic grammar (nahwu) among students (mahasantri) at the Ma’had Aly of Sunan Drajat Islamic Boarding School. Using the Asset-Based Community Development (ABCD) approach, the program empowered senior mahasantri as peer facilitators to guide small study groups through contextualized grammar lessons. The activities were conducted over a three-month period in the dormitory environment and included initial coordination, group formation, material development, intensive mentoring sessions, and periodic evaluations. The results showed a significant improvement in participants’ mastery of nahwu, the development of a collaborative learning culture, and increased confidence in reading classical Arabic texts. The program successfully integrated pesantren values with participatory learning strategies. These outcomes suggest that this model can serve as a reference for similar Arabic learning initiatives in other Islamic boarding schools